2020
DOI: 10.3390/polym12092040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Active Site Modification towards Performance Enhancement in Biopolymer κ-Carrageenan Derivatives

Abstract: This research demonstrates a one-step modification process of biopolymer carrageenan active sites through functional group substitution in κ-carrageenan structures. The modification process improves the electronegative properties of κ-carrageenan derivatives, leading to enhancement of the material’s performance. Synthesized succinyl κ-carrageenan with a high degree of substitution provides more active sites for interaction with analytes. The FTIR analysis of succinyl κ-carrageenan showed the presence of new pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
(49 reference statements)
4
22
0
Order By: Relevance
“…This could be attributed to the extra oxygen atom in succinyl-κ-carrageenan compared to the structure of κ-carrageenan as confirmed by the FTIR in research conducted by [7]. This large difference in r a was also contributed to by the high degree of substitution during synthesis of succinyl-κ-carrageenan whereby more than one hydroxyl group in pristine κ-carrageenan was substituted with the higher oxygen atom succinyl group [7]. This research pattern was reported previously, whereby adding oxygen-containing compounds increases the surface roughness up to 15 times compared to precursor compound [4,[15][16][17].…”
Section: Surface Studies Of Sensing Materials For Lsprmentioning
confidence: 78%
See 4 more Smart Citations
“…This could be attributed to the extra oxygen atom in succinyl-κ-carrageenan compared to the structure of κ-carrageenan as confirmed by the FTIR in research conducted by [7]. This large difference in r a was also contributed to by the high degree of substitution during synthesis of succinyl-κ-carrageenan whereby more than one hydroxyl group in pristine κ-carrageenan was substituted with the higher oxygen atom succinyl group [7]. This research pattern was reported previously, whereby adding oxygen-containing compounds increases the surface roughness up to 15 times compared to precursor compound [4,[15][16][17].…”
Section: Surface Studies Of Sensing Materials For Lsprmentioning
confidence: 78%
“…Due to the increased electronegative active site in succinyl-κ-carrageenan, it is expected the succinyl-κ-carrageenan operates better than the pristine κ-carrageenan LSPR sensor. The succinyl-κ-carrageenan was established in a report by Bakar et al [7]; thus, molecular characterization is not reported in this work. This research focuses on studying the physicochemical properties of succinylκ-carrageenan and evaluating its performance as a potential active material for the NH 4 + LSPR sensor.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations